Designing a 3D Animation-Based Tutorial Video for Preserving the Traditional Games of Congklak - Andrian, Jason; Syahputra, Bayu; Pratama, Jimmy (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Congklak is one of the traditional games that has become an important part of Indonesia's cultural heritage. The game entertains and teaches social values, strategic thinking, and basic skills such as counting. However, along with the development of technology and the emergence of modern games, the popularity of congklak has faded, especially among the younger generation. This research aims to develop a 3D animation-based tutorial video as a medium for preserving congklak by integrating traditional elements and modern technology. The research method utilizes a Research and Development (R&D) approach with a Multimedia Development Life Cycle (MDLC) framework. The results indicate that the developed animation video effectively engages young generations, raises cultural awareness, and provides broad accessibility through digital platforms. This study concludes that 3D animation can be an effective tool for preserving traditional games such as congklak.